2019
DOI: 10.1021/acs.energyfuels.8b04083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soot from the Use of Butanol Blends in a Euro 6 Diesel Engine

Abstract: The use of advanced fuels must increase from 0.5 to 3.6 in internal combustion engines according to the forthcoming European directive. In this frame, alcohols that can be obtained from waste or lignocellulosic materials with advanced production techniques may play an important role in the future. This work focuses on the effect of the use of butanol as a blend component on the properties of soot emmited from compression ignition engines. This knowledge is essential to decide the strategy to carry out a proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Similar results have been reported in previous studies. 29,30,71 Li et al 71 investigated the soot morphology in a laminar diffusion flame fueled with n-heptane, n-butanol, and H50B50 (50% n-heptane and 50% n-butanol, v/v), respectively. Their results showed that as the n-butanol content in blended fuels increased, smaller aggregates and primary particles were produced.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results have been reported in previous studies. 29,30,71 Li et al 71 investigated the soot morphology in a laminar diffusion flame fueled with n-heptane, n-butanol, and H50B50 (50% n-heptane and 50% n-butanol, v/v), respectively. Their results showed that as the n-butanol content in blended fuels increased, smaller aggregates and primary particles were produced.…”
Section: Methodsmentioning
confidence: 99%
“…49 The D3 band is a representation of the vibration of the amorphous carbon. 29 Correspondingly, I D1 /I G (intensity ratio of the D1 band to the G band) and A D1 /A G (area ratio of the D1 band to the G band) are used to represent the degree of graphitization and the degree of disorder for particles, respectively. The higher the value of I D1 /I G is, the lower the degree of graphitization is.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulations on PM emission are imposed stricter in diesel engines [120][121][122]. In gasoline engines, however, laws and protocols have not been set up for PM emission.…”
Section: Particulate Matter (Pm) Emissionmentioning
confidence: 99%